Geografija v antiki in prikazi slovenskega ozemlja iz tega časa - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2017)
The paper presents the development of geography in Classical antiquity by means of combining the findings in foreign and native expert literature. Classical findings, both theoretical and methodological, are the basis which has supported the development of this discipline throughout the following centuries. The broader area of the present-day Slovenian territory was poorly known in Classical antiquity, in particular the inland parts of the countries around the Northern Adriatic Sea.
Keywords: antika; classical antiquity; Jadran; Slovenia; Slovenija; viri; zgodovinska geografija